Health Education: the Effective Handwashing for Early Childhood at Al-Shafa Kindergarten Deli Serdang Regency in 2024 - Sofia Diaz, Aya; Ginting, Keleng Ate; Ritonga, Rahmad Ramadhan; Tampubolon, Regina Elianda; Purba, Sri Ulina (JURNAL PENGMAS KESTRA (JPK), 2025)
habits have not reached their full potential. Washing hands properly is one of the important yet sometimes overlooked hygiene and healthy living practices. Initial observations at Al-Shafa Kindergarten revealed that most students were unable to perform efficient handwashing techniques according to health standards and were unaware of critical times to wash their hands. This can increase the possibility of disease transmission from unclean hands. The purpose of community service is to build good living habits that can stop the spread of disease through dirty hands. The activity method uses an educational and participatory approach through interactive counseling methods, demonstrations, and direct practice, which are designed according to the characteristics of early childhood. Community service was carried out at Al-Shafa Kindergarten, Lubuk Pakam, Deli Serdang Regency, with 16 children. The results of the Community Service activity showed that 81.3% of children were able to mention important times to wash their hands and 75% of children were able to follow the six steps to wash their hands correctly. This shows that this Community Service activity has achieved a success rate (78.15%) in forming children's understanding and basic skills about PHBS. Health education activities on effective hand washing at Al-Shafa Kindergarten have succeeded in increasing the knowledge and skills of early childhood in maintaining hand hygiene. Interactive, fun, and age-appropriate learning approaches have proven effective in forming clean living behaviors from an early age. The involvement of teachers and the school environment is an important supporting factor in the success of this activity. It is hoped that this education can be the beginning of positive habits that are sustainable in the school environment and at home.